2018
DOI: 10.5005/jp-journals-10006-1617
|View full text |Cite
|
Sign up to set email alerts
|

Outlet Forceps Delivery: Role in Modern Obstetric Practice

Abstract: Aim:The dramatic rise of cesarean section rate is a global problem. The forceps delivery has also led to numerous litigations due to poor fetal and sometimes maternal outcome. Still, it is having a prominent role to reduce the rate of cesarean section deliveries. The aim of this study was to assess feto maternal outcome in outlet forceps delivery.Methods: A prospective cohort study of 92 patients who delivered by outlet forceps conducted in the department of obstetrics and gynecology,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Philip et al, Jaiswal et al and Iyengar et al also found that most babies were healthy and appropriate for gestational age. 12,13,15 As shown in Table 6, the most common indication was fetal distress, found in 54.7% patients, followed by maternal exhaustion in 28.5% and prolonged second stage in 16.6% patients. Similar results were also found by Jaiswal et al, Mishra et al, Philip et al 1,12,13 There was no neonatal death in our study.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Philip et al, Jaiswal et al and Iyengar et al also found that most babies were healthy and appropriate for gestational age. 12,13,15 As shown in Table 6, the most common indication was fetal distress, found in 54.7% patients, followed by maternal exhaustion in 28.5% and prolonged second stage in 16.6% patients. Similar results were also found by Jaiswal et al, Mishra et al, Philip et al 1,12,13 There was no neonatal death in our study.…”
Section: Discussionmentioning
confidence: 96%
“…12,13,15 As shown in Table 6, the most common indication was fetal distress, found in 54.7% patients, followed by maternal exhaustion in 28.5% and prolonged second stage in 16.6% patients. Similar results were also found by Jaiswal et al, Mishra et al, Philip et al 1,12,13 There was no neonatal death in our study. We have sent all the babies delivered by forceps routinely for observation and transferred to mother within 24-48 hours.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation